Evaluation of a flow cytometry-based surrogate assay (FlowSA) for the detection of SARS-CoV-2 in clinical samples - Vinit Upasani; Marjolein Knoester; Daniele Pantano; Lili Gard; Jolanda M. Smit; Bernardina T.F. van der Gun; Adriana Tami; Izabela A. Rodenhuis-Zybert (Journal of Clinical Virology Plus)
Introduction: The current diagnostic methods for SARS-CoV-2 rely on quantitative RT-PCR. However, the presence of viral RNA in samples does not necessarily reflect the presence of an infectious virus. Therefore, the reliable detection of infectious SARS-CoV-2 in clinical samples is necessary to limit viral transmission. Methods: We developed a flow cytometry-based surrogate assay (FlowSA), wherein the presence of infectious SARS-CoV-2 was detected using virus nucleocapsid-specific antibodies. Results: We showed that FlowSA allows the detection of a wide range of viral titers of multiple SARS-CoV-2 variants. Furthermore, the assay was successfully used to detect infectious SARS-CoV-2 in nasopharyngeal swabs from SARS-CoV-2 positive individuals, including those with high Ct values. Notably, FlowSA identified the presence of infectious SARS-CoV-2 in biological specimens that scored negative for cytopathic effect (CPE) in cell culture and would otherwise be considered negative. Conclusion: We propose that FlowSA can be adopted as an alternative to conventional CPE methods for viral diagnostics.